2015
DOI: 10.1111/jcpe.12409
|View full text |Cite
|
Sign up to set email alerts
|

Single versus double flap approach in periodontal regenerative treatment

Abstract: When combined with rhPDGF-BB and β-TCP, the SFA may result in similar clinical outcomes, better quality of early wound healing, and lower pain and consumption of analgesics during the first postoperative days compared to the DFA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
98
1
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(114 citation statements)
references
References 32 publications
10
98
1
5
Order By: Relevance
“…Previous randomized clinical trials have clearly demonstrated that an SFA may optimize clinical outcomes compared with a conventional double‐flap approach when used with 15 or without 9 regenerative devices, while limiting the level of post‐surgery pain and discomfort 15 . Adjunctive use of a CTG unavoidably results in a more technically demanding procedure and increases the intra‐ and postoperative morbidity due to the need for an additional surgical site for graft harvesting.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous randomized clinical trials have clearly demonstrated that an SFA may optimize clinical outcomes compared with a conventional double‐flap approach when used with 15 or without 9 regenerative devices, while limiting the level of post‐surgery pain and discomfort 15 . Adjunctive use of a CTG unavoidably results in a more technically demanding procedure and increases the intra‐ and postoperative morbidity due to the need for an additional surgical site for graft harvesting.…”
Section: Discussionmentioning
confidence: 99%
“…Presurgery and surgical procedures were performed by expert periodontal surgeons (LT, LM, RF, GR) involved in previous clinical trials on SFA 7‐12,15 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations